Do Politicians Change Public Attitudes? - Magnus Carlsson; Gordon B. Dahl; Dan-Olof Rooth (Institute for the Study of Labor (IZA), 2016)
A large theoretical and empirical literature explores whether politicians and political parties change their policy positions in response to voters' preferences. This paper asks the opposite question: do political parties affect public attitudes on important policy issues? Problems of reverse causality and omitted variable bias make this a difficult question to answer empirically. We study attitudes towards the signature policies of small parties in Sweden using panel data from 290 municipal election districts. To identify causal effects, we take advantage of large nonlinearities in the function which assigns council seats, comparing otherwise similar elections where one party either barely wins or loses an additional seat. We estimate that a one seat increase for the anti-nuclear party reduces support for nuclear energy in that municipality by 3.3 percentage points. In contrast, when an anti-immigration or far left politician gets elected, negative attitudes towards immigration decrease by 4.8 percentage points and support for a six hour workday falls by 3.2 percentage points, respectively, in opposition to each party's policy position. Mirroring these attitudinal changes, the anti-nuclear party receives more votes in the next election after gaining a seat, while the anti-immigrant and far left parties lose their incumbency advantage. Exploring two possible mechanisms, we find evidence that when the anti-immigrant party gains an extra seat, they draw in lower quality politicians and receive negative local newspaper coverage. These findings have important implications for the theory and estimation of how voter preferences enter into electoral and political economy models.
Keywords: D72; H70; 330; voter preferences; incumbency effects; media influence